1999
DOI: 10.1002/(sici)1097-0134(19990901)36:4<383::aid-prot2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Early events in the folding of an amphipathic peptide: A multinanosecond molecular dynamics study

Abstract: Folding of the capped LQQLLQQLLQL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 115 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…Complicated interfacial environments such as lipid bilayers present great obstacles to complete sampling of peptide conformations in MD simulations [47,48]. In this sense, it is not surprising that the helical starting conformations remain stable over the timescale of our simulations.…”
Section: Discussionmentioning
confidence: 95%
“…Complicated interfacial environments such as lipid bilayers present great obstacles to complete sampling of peptide conformations in MD simulations [47,48]. In this sense, it is not surprising that the helical starting conformations remain stable over the timescale of our simulations.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous computational study of interfacial folding involving an undecamer peptide consisting of a sequence of Leu and Gln residues capable of forming an amphipathic ␣-helix, it was shown that if the peptide was placed on the water side in a nonamphipathic ␤-sheet conformation, the peptide would still migrate to the water/hexane interface and adopt a nonhelical amphipathic conformation with nearly optimal amphipathy (Chipot et al, 1999). Almost no nonamphipathic conformations were observed at the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Although the partitioning of residues into one of the phases can initiate secondary structure formation, transitions between different amphipathic structures at an interface could require the surmounting of high free energy barriers. Nonoptimized folded structures with a satisfactory partitioning of the residues may represent local minimum on the free energy surface and impede folding (Chipot et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The explosion of computing capacity enabled us to simulate folding of peptides or small proteins in explicit solvent (71). Daura et al (70,72,73) were able to fold and unfold a b-heptapeptide in methanol, Chipot et al to fold some helical peptides at a water/hexane interface (74,75). In 1998, Duan and Kollman brought a milestone in explicit simulations by describing an early folding event of a small protein (the villin headpiece) in a microsecond molecular dynamics (76).…”
Section: Introductionmentioning
confidence: 99%